2001
DOI: 10.1183/09031936.01.00229001
|View full text |Cite
|
Sign up to set email alerts
|

Role of T- and B-lymphocytes in pulmonary host defences

Abstract: Pulmonary infectious diseases cause significant morbidity and mortality in both industrialized and developing countries.Adaptive immune responses are required to defend the lung against pathogens that survive in normal macrophages and extracellular organisms that evade phagocytosis. Microbes initiate both innate immune responses and specific adaptive immune responses.Innate immune response molecules regulate T-lymphocyte differentiation. Activated T-lymphocytes provide cytokines, which activate macrophages and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…These antibodies have an important role in the protection against pneumococcal infection since opsonizing IgG antibodies are important for complement fixation and for enhancing the efficiency of macrophage killing. This immune activation also induces the production at the systemic level of antibodies responsible for preventing the passage of S. pneumoniae to the blood and their subsequent dissemination [34].…”
Section: Effect On Immunocompetent Hostsmentioning
confidence: 99%
“…These antibodies have an important role in the protection against pneumococcal infection since opsonizing IgG antibodies are important for complement fixation and for enhancing the efficiency of macrophage killing. This immune activation also induces the production at the systemic level of antibodies responsible for preventing the passage of S. pneumoniae to the blood and their subsequent dissemination [34].…”
Section: Effect On Immunocompetent Hostsmentioning
confidence: 99%
“…Besides, systemic antibody transudation increases during inflammatory reactions when vascular permeability is increased, which enhances pulmonary clearance of pathogenic microorganisms. 36 Knowledge of the mechanisms involved in the lung immune response against respiratory pathogens is necessary because it is in this context that recombinant vaccines will have to exert their preventive effect.…”
Section: 24mentioning
confidence: 99%
“…This immune activation also induces the production at the systemic level of antibodies responsible for preventing the passage of pathogens to the blood and their subsequent dissemination (Moore, Moore, & Toews, 2001). Our experiments demonstrated that treatment with YP improved the production of anti-pneumococcal IgG in BAL and serum.…”
Section: Discussionmentioning
confidence: 73%